Tuning the Inter-Chromophore Electronic Coupling in Perylene Diimide Dimers with Rigid Covalent Linkers - Guo Yu; Yixuan Gao; Yonghang Li; Yiran Tian; Xiaoyu Zhang; Yandong Han; Jinsheng Song; Wensheng Yang; Xiaonan Ma (Molecules)
The organic multi-chromophore system has been increasingly attractive due to the potential optoelectronic applications. The inter-chromophore electronic coupling (EC), i.e., JCoul and JCT, plays a critical role in determining the relaxation path of the excited state. However, the molecular designing strategy for effective tuning of inter-chromophore EC is still challenging. In this computational work, we designed a series of perylene diimides (PDI) covalent dimers with rigid linking cores containing thiophene (Th) or phenyl (Ph) fragments and performed corresponding theoretical investigation to analyze the inter-PDI electronic coupling. Vibrational analysis indicated that the minimized excited state structural relaxation (ES-SR) can ensure the rigid inter-PDI geometry pre-defined by the topological characteristic of linking cores, leading to comparable |JCoul| on S0 and S1 states. The saddle-shaped linking cores allow collaborative tuning of inter-PDI dihedral (α) and slipping (θ) angles, leading to effective tuning of inter-PDI |JCoul| = 0–1000 cm−1. Our work provides a new molecular designing strategy for effective tuning of inter-chromophore EC for organic chromophores. By using a rigid inter-chromophore structure, the ignorable ES-SR allows simplified molecular designing without considering the plausible geometric difference between S1 and S0 states, which might be useful for future applications in organic optoelectronics.